PENGELOLAAN SUMBER DAYA AIR DI DUKUH KALIURANG:: Perspektif Ekonomi Islam (Jurnal Penelitian, 2012)
In Islamic economics, water is considered a blessing from God that gives and sustains life, and purifies humankind and the earth. It belongs to the community as a whole—no individual literally owns water. As a sustainer of life, it is important to manage and distribute water properly so that all communities can access it for consumption, such as drinking and washing, and for production, such as farming. Unfortunately, water management in Kaliurang hamlet of Kembanglangit village is not carried out properly, so the community living there cannot access sufficient water and suffers from water and food crises. This article discusses the problem of water management there from the perspective of Islamic economics's view.
Keywords: sumber penghidupan; barang publik; milik bersama; prioritas utama; syura; partisipasi masyarakat